2017
DOI: 10.1115/1.4035162
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Vane Endwall Film Cooling With Slashface Leakage and Discrete Hole Configuration

Abstract: Turbine vanes are typically assembled as a section containing single or double airfoil units in an annular pattern. First stage guide vane assembly results in two common mating interfaces: a gap between combustor and vane endwall and another resulted from the adjacent sections, called slashface. High pressure coolant could leak through these gaps to reduce the ingestion of hot gas and achieve certain cooling benefit. As vane endwall region flow field is already very complicated due to highly three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Thus, an appropriate cooling scheme is important for protecting the vane endwall efficiently. Chowdhury et al 23 measured the endwall film cooling effectiveness under different discrete hole arrangements. Li et al 24 studied the film cooling distribution with six rows of cylindrical holes placed at different axial locations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an appropriate cooling scheme is important for protecting the vane endwall efficiently. Chowdhury et al 23 measured the endwall film cooling effectiveness under different discrete hole arrangements. Li et al 24 studied the film cooling distribution with six rows of cylindrical holes placed at different axial locations.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the cooling jet from the upstream slot is greatly impacted by crossflow. Chowdhury et al [6] investigated the influence of the mass flow ratio of the coolant to the mainstream utilizing pressure-sensitive coating technology (PSP). The results show that increasing the mass flow ratio can improve endwall cooling performance by preventing the development of the horseshoe vortex.…”
Section: Introductionmentioning
confidence: 99%
“…As shown above, the pressure side hot region endures high level of thermal load and needs advanced cooling schemes to ensure the safe operation [16,17]. Chowdhury et al [22] introduced two rows of film holes near the pressure side. The experimental results showed that the typical uncooled region was reduced.…”
Section: Introductionmentioning
confidence: 99%